Lightning Mapping Array flash detection performance with variable receiver thresholds. Issue 14 (28th July 2016) - Chmielewski, Vanna C.; Bruning, Eric C.
Abstract: This study characterizes Lightning Mapping Array performance for networks that participated in the Deep Convective Clouds and Chemistry field program using new Monte Carlo and curvature matrix model simulations. These open‐source simulation tools are readily adapted to real‐time operations or detailed studies of performance. Each simulation accounted for receiver threshold and location, as well as a reference distribution of source powers and flash sizes based on thunderstorm observations and the mechanics of station triggering. Source and flash detection efficiency were combined with solution bias and variability to predict flash area distortion at long ranges. Location errors and detection efficiency were highly dependent on the station configuration and thresholds, especially at longer ranges, such that performance varied more than expected across different networks and with azimuth within networks. Error characteristics matched prior studies, which led to an increase in flash distortion with range. Predicted flash detection efficiency exceeded 95% within 100 km of all networks. Key Points: LMA location errors and detection efficiency are highly dependent on the station configuration and thresholds, especially at longer ranges Performance varied greatly across different DC3 networks and with azimuth in each, but overall error characteristics matched prior studies Predicted flash detection efficiency exceeded 95% within 100 km of all DC3 networks, and these flashes are distorted more at larger ranges